Development of alpha hemolytic verotoxigenic Escherichia coli vaccine: Verotoxic antibody responses in experimental animals, mice, rabbits and dairy cows - ., Supar; Peorwadikarta, B; Kurniasih, Nina; ., Djaenuri (Indonesian Journal of Animal and Veterinary Sciences, 1999)
Escherichia coli isolates showing alpha hemolytic on blood agar were found in calves with bloody diarrhoea from Bandung, Sukabumi and Bogor. Three E. coli isolates designated as (B34c, B909, B910) were pathogenic for mice and selected for vaccine candidates. Crude supernatant of tryptic soy broth (TSB) cultures precipitated with saturated ammoniumsulphate caused cytopathic effect on vero cell line. For vaccine preparation the isolates were grown on tryptic soy agar (TSA). Whole cell inactive vaccine containing equal proportion of each isolate was prepared and emulsified in aluminum hydroxide gel at a final concentration of 1.5% and cell concentration equal to the tube number 10 of MacFarland standard. Mice and rabbits were injected subcutaneously of monovalent vaccine with the dose of 0.2 ml and 1 ml respectively. Four weeks later mice or rabbits were boostered with the same dose. Before injection each animal was bleed, subsequently every two weeks period up to 4 weeks after the second injection. The sera were separated and kept at -20oC up to serological assay with an enzyme linked immunoassay (ELISA) was done. Vaccinated mice with VTEC were challenged with homologous isolate did not die, where as 60% of unvaccinated mice died within 2 days post challenged. Pregnant cows were given 2 doses of three valent vaccine 6 weeks and again 2 weeks before expected date of calving. Calves born were given colostrum and milk of the own mother. The three day old calf was challenged with three isolates of verotoxigenic E. coli studied. Calves born from vaccinated cows did not show diarrhoea at post challenged, whereas calf from unvaccinated cow demonstrated bloody diarrhoea at post challenged. From the experimental animals (mice and calves) demonstrated the presence of protection against challenged. The antiverotoxic antibody probably involved in important role of immunoprotection. These were supported by the presence of high titer anti verotoxic antibody in serum of experimental animals (mice and cows), as well as in experimental rabbits, but none in the unvaccinated animals. Â  Key words: E. coli, alpha hemolytic, verotoxic, dysentery, vaccine